PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA PERAWAT RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Aldisal Aranda; Alvi Purwanti Alwie; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research conducted to analyze The Influence of Transformasional Leadership, Organizational Culture and Job Satisfaction on Nurse Organizational Commitment (Study at Islam Ibnu Sina Hospital Pekanbaru.) There are independent variables in this research such as Transformasional Leadership (X1), Organizational Culture (X2), Job Satisfaction (X3) and Nurse Organizational Commitment (Y) as dependent variabel. The population of this study were nurse at Islam Ibnu Sina Hospital Pekanbaru and total sample were 108 peoples. Multiple regression method are chosen for data analysis by SPSS version 21. The result of this research shows that Transformasional Leadership, Organizational Culture and Job Satisfaction both simultaneously and partially had effects with Nurse Organizational Commitment at Islam Ibnu Sina Hospital Pekanbaru.. Organization Culture were dominant factor towards Nurse Organizational Commitment. The expectation of this research is Islam Ibnu Sina Hospital Pekanbaru should improve Transformasional Leadership, Organizational Culture and Job Satisfaction among nurse in order to improve Nurse Organizational Commitment.Keywords: Transformasional Leadership, Organizational Culture, Job Satisfaction, Nurse Organizational Commitment.